A Comparative Study of Systolic and Diastolic Mechanical Synchrony in Canine, Primate, and Healthy and Failing Human Hearts - Zhu, Tiangang; Lei, Ming; Wang, Zhilong; Zhang, Rongli; Zhang, Yan; Jin, Wenying; Yu, Chao; Huang, Christopher L.-H.; Liu, Dongyue; Zheng, Wen; Liu, Yuli; Quan, Xin; et al. (Frontiers in Cardiovascular Medicine, 2021)
Abstract Aim: To investigate systolic and diastolic mechanical synchrony in canine, primate and health subjects and failing human hearts. Methods and Results: left and right ventricular mechanical function were examined by Pulse-wave Doppler in 15 beagle dogs, 59 rhesus monkeys, 100 healthy human subjects and 39 heart failure patients. Pre-ejection periods (RVPEP and LVPEP) and diastolic opening times (Q-MVe and Q-TVe) of right and left ventricle were measured in three species of above. The occurrence of left ventricular mechanical delay in systole (LVMDs) was identified when RVPEP < LVPEP. Conversely, the existence of a right ventricular mechanical delay in systole (RVMDs) was identified when RVPEP > LVPEP. Similarly, the existence of left ventricular mechanical delay in diastole (LVMDd) was identified when Q-MVe > Q-TVe, and the existence of a right ventricular mechanical delay in diastole (RVMDd) was identified when Q-MVe < Q-TVe.The healthy hearts showed greater left than right delay times and therefore positive systolic and diastolic IVMD (IVMDs, IVMDd). Alterations in HF patients resulted in marked increases in both IVMDs and reversals in IVMDd. Diastolic mechanic asynchrony appears to be negatively correlated with LVEF in patients with heart failure. Conclusion: IVMDs and IVMDd have potential clinical implications in particular for setting effective cardiac resynchronization therapy procedures for treating HF. Inter-ventricular diastolic mechanic asynchrony can be a novel valuable parameter used for optimizing cardiac resynchronization therapy (CRT) in patients with heart failure.